2018
DOI: 10.1044/2017_jslhr-s-16-0379
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Misarticulations on Children's Word Identification and Processing

Abstract: https://doi.org/10.23641/asha.5965510.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 42 publications
(56 reference statements)
3
18
0
Order By: Relevance
“…Children who interact with others their age (e.g., in a day care or preschool setting) likely have extensive experience with another type of variability-developmentally appropriate speech sound misarticulations. Our previous study in this line explored the role of children's experience with speech sound variability and examined whether the commonness of the phoneme substitute (i.e., frequency of occurrence in typical development according to normative data) impacted children's identification of words as real objects or as novel objects (Krueger, Storkel, & Minai, 2018). To examine commonness, we conducted a series of three experiments in which children heard three types of tokens.…”
Section: Commonness Of Variabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Children who interact with others their age (e.g., in a day care or preschool setting) likely have extensive experience with another type of variability-developmentally appropriate speech sound misarticulations. Our previous study in this line explored the role of children's experience with speech sound variability and examined whether the commonness of the phoneme substitute (i.e., frequency of occurrence in typical development according to normative data) impacted children's identification of words as real objects or as novel objects (Krueger, Storkel, & Minai, 2018). To examine commonness, we conducted a series of three experiments in which children heard three types of tokens.…”
Section: Commonness Of Variabilitymentioning
confidence: 99%
“…Across each of the three experiments in this study, preschoolers selected visual representations of real objects significantly more when they heard common misarticulations than when they heard uncommon misarticulations. Despite the consistent Krueger et al (2018), used in this study. Clicking "start" initiates the trial, and children selected real objects or novel objects in response to auditory presentation of stimuli.…”
Section: Commonness Of Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse-tracking lexical-decision paradigm In the past few years, previous studies (Anderson et al, 2011;Cargill et al, 2007;Hermens, 2018;Krueger et al, 2018;Schroeder & Verrel, 2014) have shown that computer mouse tracking and other motor-tracking techniques (e.g., finger tracking or three-dimensional reach tracking) are feasible for studying language processing in both younger and older children (for a more comprehensive overview of using the mouse-tracking technique with child participants, see Erb, 2018). In particular, the mouse-tracking lexical-decision paradigm has proven to be a powerful and popular research tool for assessing the cognitive processing that underlies visual word recognition (e.g., Barca & Pezzulo, 2012, 2015.…”
Section: The Effects Of Vocabulary Knowledge and Agementioning
confidence: 99%